Turning gangsters into allies: the American way of war in Northern Afghanistan. (2nd January 2019) - Dearing, Matthew P.
ABSTRACT: The American way of war in Afghanistan presents a conundrum for proponents of 21st-century state-building projects. How can liberal peace proponents engage in efficient state building without sacrificing their ideals? The US learned that state-building allocates a degree of command and control to powerbrokers operating in the shadows to launder aid money, traffic illicit narcotics, and engage in extrajudicial punishments. These clients failed to represent the liberal values foreign patrons endorsed, because the latter not only offered resources without conditions but also rewarded bad behavior. This issue is examined by looking at the case of post-2001 northern Afghanistan, where powerful warlords should have held greater control over their paramilitary forces, limited predatory behavior, and built stronger relationships with the community. Instead, warlords-turned-statesmen expanded their material and social influence in the north, while holding onto the informal instruments of racketeering and patronage that overwhelmed Western ideals and shaped the predatory state present in Afghanistan today. Moreover, paramilitaries were influenced by material, social, and normative incentives that rewarded violent and predatory behavior and further eroded already weak community control mechanisms at the subdistrict level.